Epibrassinolide Prevents Tau Hyperphosphorylation via GSK3 Beta Inhibition in Vitro and Improves Caenorhabditis Elegans Lifespan and Motor Deficits in Combination With Roscovitine - Gürkan, Ajda Çoker; OKUMUŞ, OSMAN ORÇUN; YENİGÜN, TUĞBA; ÖZBEY, UTKU; KARA, MELİSSA; Ünsal, Narcin Palavan; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Springer Wien, 2021)
Glycogen synthase kinase 3 beta (GSK3 beta) is considered an important element of glycogen metabolism; however, it has many other regulatory roles. Changes in the GSK3 beta signaling mechanism have been associated with various disorders, such as Alzheimer's disease (AD), type II diabetes, and cancer. Although the effects of GSK3 beta inhibitors on reducing the pathological effects of AD have been described, an effective inhibitor has not yet been developed. Epibrassinolide (EBR), a brassinosteroid (BR), is structurally similar to mammalian steroid hormones. Our studies have shown that EBR has an inhibitory effect on GSK3 beta in different cell lines. Roscovitine (ROSC), a cyclin-dependent kinase (CDK) inhibitor, has also been identified as a potential GSK3 inhibitor. Within the scope of this study, we propose that EBR and/or ROSC might have mechanistic action in AD models. To test this hypothesis, we used in vitro models and Caenorhabditis elegans (C. elegans) AD strains. Finally, EBR treatment successfully protected cells from apoptosis and increased the inhibitory phosphorylation of GSK3 beta. In addition, EBR and/or ROSC treatment had a positive effect on the survival rates of C. elegans strains. More interestingly, the paralysis phenotype of the C. elegans AD model due to A beta 42 toxicity was prevented by EBR and/or ROSC. Our findings suggest that EBR and ROSC administration have neuroprotective effects on both in vitro and C. elegans models via inhibitory GSK3 beta phosphorylation at Ser9.
Keywords: Epibrassinolide; Roscovitine; Alzheimer’s Disease; Tau